Study of Cerotelium fici rust on Ficus sp. of forest nursery - S.C. SILAWAT, HEMANT PATHAK*, H.N. SATYA and (Indian Phytopathology, 2016)
Ficus religiosa L., Ficus benghalensis L. and Ficus racemosa L. are large evergreen trees found throughout India, wild and cultivated. They are popular indigenous system of medicine like Unani, Ayurveda and Homeopathy. The various parts of the plants like stem bark, fruits, buds, latex are used in treatment of different diseases. The tree legume is prone to various seedling and foliage diseases found in nurseries. This study reported incidence of rust caused by Cerotelium fici on seedling of three Ficus species, maintained in nursery seedling beds of Forest Research and Extension Circle Indore, India.